2008
DOI: 10.1007/s10706-008-9187-2
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Limit Equilibrium Approach for Calculation of Ultimate Bearing Capacity of Shallow Foundations on Two-Layered Granular Soils

Abstract: The bearing capacity of shallow foundations in a non-homogeneous soil profile has been a challenging task in geotechnical engineering. In this paper, a limit equilibrium method is used for calculating bearing capacity factors of shallow foundations constructed on a two-layered granular soil profile. The main objective has been to determine the ultimate bearing capacity computed from equivalent bearing capacity factors N q and N c and comparing that with numerical analysis using finite element methods. It will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 7 publications
2
22
0
Order By: Relevance
“…They checked the results obtained by using the Coulomb approach with the results obtained from Finite Element analyses. Ghazavi and Eghbali (2008) concluded that the results obtained from the Finite Element analysis matched very well with the results obtained from the Coulomb formulation. Michalowski (1998) stated that as failure occurs, the direction of a flexible reinforcement will change and try to align itself with the failure plane.…”
Section: Bearing Capacity Based On Coulomb Theorysupporting
confidence: 63%
See 2 more Smart Citations
“…They checked the results obtained by using the Coulomb approach with the results obtained from Finite Element analyses. Ghazavi and Eghbali (2008) concluded that the results obtained from the Finite Element analysis matched very well with the results obtained from the Coulomb formulation. Michalowski (1998) stated that as failure occurs, the direction of a flexible reinforcement will change and try to align itself with the failure plane.…”
Section: Bearing Capacity Based On Coulomb Theorysupporting
confidence: 63%
“…They adapted this modified Coulomb method to calculate the seismic bearing capacities of footings. Ghazavi and Eghbali (2008) also took the simple Coulomb method proposed by Lambe and Whitman (1969) and adapted it to a two layered soil. They checked the results obtained by using the Coulomb approach with the results obtained from Finite Element analyses.…”
Section: Bearing Capacity Based On Coulomb Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…[9] and Potts [6]. It should be noted that in both cases same displacement value has been applied on top of soil.…”
Section: Effect Of Materials Properties On Magnitude and Direction Of mentioning
confidence: 99%
“…Methods of solving bearing capacity of footing are classified in four major approaches: limit equilibrium, limit analysis approach, semi empirical approach and finite element method. In recent years, Finite Element Method (FEM) have been widely using in geotechnical studies to investigate soil behaviour [3][4][5][6]. In practice, for bearing capacity analysis engineers are seeking less complicated solutions to simplify computations as experimental analysis is time consuming and commonly used solutions such as limit equilibrium are no longer applicable.…”
Section: Introductionmentioning
confidence: 99%